Recovery of ammonium from stormwater by ion exchange: Purifying seepage water in laboratory and pilot scales - Jianzhi Song; Jari Heinonen; Tuomo Sainio (Desalination and Water Treatment)
Ammonium removal from seepage water (representative stormwater) by ion exchange was investigated experimentally on laboratory and pilot scales. The results present the removal of ammonium from the worst-case scenario of stormwater, which is seepage water. Ammonium removal was efficiently accomplished with commercial resin CS16GC in proton and sodium forms. With the resin in H+ form, simultaneous removal of Na+, K+, Ca2+, and Mg2+ was achieved, whereas with the resin in Na+ form, other metals except Na+ were removed. Resin regeneration could be done efficiently with 2 mol/L HCl and 2 mol/L NaCl. Cyclic (7 cycles) ammonium removal runs were conducted with the CS16GC resin in Na+ form on both laboratory and pilot scale. Qualitatively, the results obtained from the cyclic runs done on laboratory and pilot scales were similar; however, some differences were observed because of slightly different feed compositions. In the pilot-scale run, 95–100% ammonium removal was obtained. The performance of the commercial resin was efficient compared with novel materials reported in the literature in an analysis method proposed by the authors. Ion exchange–based ammonium removal was shown to be an efficient method, and further investigation on the long-term stability of the process is warranted.